TELAAH PEMBENTUKAN INDIVIDU MUSLIM MENURUT AHMAD SYALABI DALAM KITAB AL-MUJTAMA’ AL-ISLAMY - Aniqotul Azizah, Noris; Rohma Fatul Fauziah, Asmah (Universitas Islam Lamongan, 2024)
This research was motivated by the researcher's anxiety about the character or individual of a Muslim who is currently experiencing damage due to developments over time and a lack of character education. When an individual ignores character education, there will be a lot of confusion regarding morals, especially for Muslims. Education for individual formation itself has been explained in the book Al-Mujtama' Al-Islamy by Ahmad Syalabi, which clearly explains the characteristics of Muslim individuals. This research was conducted with the aim of explaining or describing the formation of Muslim individuals based on the book Al-Mujtama' Al-Islamy written by Ahmad Syalabi. This type of research is library research. Based on the findings made by researchers, namely that the formation of Muslim individuals consists of two factors, the first factor is tolerance, and the second factor is emulating the characteristics of the Prophet Muhammad SAW.